Effects of Sweet Cherry Polyphenols on Enhanced Osteoclastogenesis Associated With Childhood Obesity - Filomena Corbo; Giacomina Brunetti; Pasquale Crupi; Sara Bortolotti; Giuseppina Storlino; Laura Piacente; Alessia Carocci; Alessia Catalano; Gualtiero Milani; Graziana Colaianni; Silvia Colucci; Maria Grano; et al. (Frontiers in Immunology, 2019)
Childhood obesity is associated with the development of severe comorbidities, such as diabetes, cardiovascular diseases, and increased risk of osteopenia/osteoporosis and fractures. The status of low-grade inflammation associated to obesity can be reversed through an enhanced physical activity and by consumption of food enrich of anti-inflammatory compounds, such as omega-3 fatty acids and polyphenols. The aim of this study was to deepen the mechanisms of bone impairment in obese children and adolescents through the evaluation of the osteoclastogenic potential of peripheral blood mononuclear cells (PBMCs), and the assessment of the serum levels of RANKL and osteoprotegerin (OPG). Furthermore, we aimed to evaluate the in vitro effects of polyphenol cherry extracts on osteoclastogenesis, as possible dietary treatment to improve bone health in obese subjects. High RANKL levels were measured in obese with respect to controls (115.48 ± 35.20 pg/ml vs. 87.18 ± 17.82 pg/ml; p < 0.01), while OPG levels were significantly reduced in obese than controls (378.02 ± 61.15 pg/ml vs. 436.75 ± 95.53 pg/ml, respectively, p < 0.01). Lower Ad-SoS- and BTT Z-scores were measured in obese compared to controls (p < 0.05). A significant elevated number of multinucleated TRAP+ osteoclasts (OCs) were observed in the un-stimulated cultures of obese subjects compared to the controls. Interestingly, obese subjects displayed a higher percentage of CD14+/CD16+ than controls. Furthermore, in the mRNA extracts of obese subjects we detected a 2.5- and 2-fold increase of TNFα and RANKL transcripts compared to controls, respectively. Each extract of sweet cherries determined a dose-dependent reduction in the formation of multinucleated TRAP+ OCs. Consistently, 24 h treatment of obese PBMCs with sweet cherry extracts from the three cultivars resulted in a significant reduction of the expression of TNFα. In conclusion, the bone impairment in obese children and adolescents is sustained by a spontaneous osteoclastogenesis that can be inhibited in vitro by the polyphenol content of sweet cherries. Thus, our study opens future perspectives for the use of sweet cherry extracts, appropriately formulated as nutraceutical food, as preventive in healthy children and therapeutic in obese ones.